2007
DOI: 10.1093/ajcn/86.3.790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-fat, fermented milk enriched with plant sterols on serum lipid profile and oxidative stress in moderate hypercholesterolemia

Abstract: Background: Plant sterol (PS)-enriched foods have been shown to reduce plasma LDL-cholesterol concentrations. In most studies, however, PSs were incorporated into food products of high fat content. Objective: We examined the effect of daily consumption of PSsupplemented low-fat fermented milk (FM) on the plasma lipid profile and on systemic oxidative stress in hypercholesterolemic subjects. Design: Hypercholesterolemic subjects (LDL-cholesterol concentrations ͧ130 and ͨ 190 mg/dL; n ҃ 194) consumed 2 low-fat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 34 publications
(42 reference statements)
7
58
0
4
Order By: Relevance
“…Foods with lower contents of saturated fatty acids are the order of day and in recent year's significant increase in the demand of such products have been observed. The great deal of shifting from saturated fats to unsaturated sources of oils is greatly attributed to the large number of incidences of cardiovascular diseases, hypertension, obesity, diabetes other health related disorders (Hansel et al 2007). The situation has led to the increased consumption of functional foods containing higher content of polyunsaturated fatty acids.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Foods with lower contents of saturated fatty acids are the order of day and in recent year's significant increase in the demand of such products have been observed. The great deal of shifting from saturated fats to unsaturated sources of oils is greatly attributed to the large number of incidences of cardiovascular diseases, hypertension, obesity, diabetes other health related disorders (Hansel et al 2007). The situation has led to the increased consumption of functional foods containing higher content of polyunsaturated fatty acids.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Nevertheless, HDL cholesterol and triglycerides were not affected by the consumption of the drink, which was sensorally accepted by the subjects (Weidner et al, 2008). Accordingly, many studies have demonstrated and corroborated the effectiveness of phytosterols enriching various foods; margarine (AbuMweis et al, 2008), juices (Devaraj et al, 2003), milk (Plana et al, 2008;Hansel et al, 2007), and yogurt (Plat et al, 2009), evaluating cholesterol-lowering effect when consumed in the recommended dose. Recently, a meta-analysis of 84 clinical trials was conducted evaluating the effect of the enrichment of foods with phytosterols on subjects with hypercholesterolemia.…”
Section: Hypocholesterolemic Effectsmentioning
confidence: 87%
“…Foods with lower contents of saturated fatty acids are the order of day and in recent year's significant increase in the demand of such products have been observed. The great deal of shifting from saturated fats to unsaturated sources of oils is greatly attributed to the large number of incidences of cardiovascular diseases, hypertension, obesity, diabetes, and other health-related disorders [15]. The situation has led to the increased consumption of functional foods containing higher content of PUFA.…”
Section: Discussionmentioning
confidence: 99%